Phytochemical Screening Of Methanolic Extract Of Vanda Tessellata Fraction 2 And 3 On Cell Cycle Distribution Of Colorectal Adenocarcinoma Cell Lines (Cuestiones de Fisioterapia, 2025)
Roughly 90% of malignant large bowel tumors are colorectal adenocarcinomas. Early diagnosis via screeningprograms is crucial since early-stage colorectal cancer often exhibits no symptoms. This research evaluatedthe phytochemical screening of methanolic extract of Vanda tessellata on cell cycle distribution of colorectaladenocarcinoma cell lines. The mature and fresh leaves of Vanda tessellate were collected from theDehradun, Uttarakhand in the month of October. Leaves were identified and authenticated by the botanist atCSIR-National Botanical Research Institute (NBRI), Lucknow, India. The leaves of Vanda tessellata wereextracted using petroleum ether, DCM and methanol solvent. Phytochemical screening was performed for allthe 3 extracts. Isolation of the compounds was performed using column chromatography.